Analyzing the gaps for Blockchain integration in the Colombian financial system. (Business Vision, 2024)
This research explores the challenges of integrating blockchain technology into Colombia's financial system, highlighting the regulatory, technological, and educational obstacles that hinder its effective adoption. Through a detailed analysis of in-depth interviews with a panel of experts, critical gaps were identified and strategies to overcome them were proposed. Key barriers include the lack of a clear regulatory framework, challenges in interoperability with existing financial systems, and a significant need for blockchain education. The aim is to provide solutions that enhance blockchain integration, fostering an adequate regulatory framework, the development of robust technological infrastructure, and the implementation of educational programs. These actions could enable Colombia to capitalize on the opportunities offered by blockchain for innovation and competitiveness in the global financial arena.
Keywords: Blockchain regulation; financial interoperability; cybersecurity; blockchain adoption